2020
DOI: 10.3390/psych2030015
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation for Major Depression and Obsessive-Compulsive Disorder—Discontinuation of Ongoing Stimulation

Abstract: Deep brain stimulation (DBS) is currently under research for the treatment of psychiatric disorders, e.g., obsessive-compulsive disorder (OCD) and treatment-resistant depression (TRD). Since the application of DBS in psychiatry has been in use for about 20 years, it is necessary to evaluate its long-term use now. A main issue in the long-term treatment of DBS concerns the effects of a discontinuation of stimulation due to intended as well as unintended reasons. In this contribution, the literature describing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…Future studies are necessary to test the long-term stability of the demonstrated effects with the stimulation turned on and turned off. This is highly relevant given the fact that a discontinuation of stimulation is associated with a relapse of symptoms [ 16 ] as well as a reduction of quality of life [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies are necessary to test the long-term stability of the demonstrated effects with the stimulation turned on and turned off. This is highly relevant given the fact that a discontinuation of stimulation is associated with a relapse of symptoms [ 16 ] as well as a reduction of quality of life [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…DBS of the slMFB has shown promising results in terms of rapid and sustained antidepressant effects [ 11 15 ]. Beyond that, patients subjectively reported social functioning improvements [ 13 , 16 ]. Considering that normal social functioning is crucial for a good quality of life [ 17 , 18 ], reduces the mortality risk [ 19 ] and further plays an important role in the long-term stabilization after chronic diseases [ 20 ], it can be considered an important therapeutic outcome [ 9 ].…”
Section: Introductionmentioning
confidence: 99%